Bureaucracy and the need for entrepreneurship in South Africa - P. Human (South African Journal of Business Management, 1984)
The growth of bureaucratic organization is seen as a characteristic inherent in capitalism. The concentration of economic power in South Africa is used as a measure of the extent of bureaucratization in this country. It is argued that this development is increasing and that such a development is structurally determining bureaucratic ways of thinking. Such an ethos is dysfunctional to the vitality of economic development; this problem thus warrants our attention. It is suggested that the entrepreneurial spirit is the prime mover in economic development; this way of thinking is, moreover, described and explained. It is further suggested that this way of thinking could be promoted and certain methods are proposed. It is, however, argued that much of the attention given to the entrepreneur has been misdirected to sectors of the economy which are in fact peripheral to economic development. The development of the small business sector is certainly of some importance; this sector cannot, however, solve our major problem, and that is the lack of real vitality of big business which grows by take-overs and mergers rather than by producing and distributing more wealth. This shortcoming, it is argued, is a function of the reproduction of the bureaucratic way of thinking.
Keywords: 650